The Immunomodulatory Properties of Helicobacter pylori Confer Protection Against Allergic and Chronic Inflammatory Disorders - Müller, Anne; Arnold, Isabelle; Hitzler, Iris (Frontiers in Cellular and Infection Microbiology, 2012)
Chronic infection with the gastric bacterial pathogen Helicobacter pylori causes gastritis and predisposes carriers to a high risk of developing gastric and duodenal ulcers, gastric cancer and gastric lymphoma, but has also recently been shown to protect against certain allergic and chronic inflammatory disorders. The immunomodulatory properties that allow the bacteria to persist for decades in infected individuals in the face of a vigorous, yet ultimately non-protective, innate and adaptive immune response may at the same time confer protection against allergies, asthma and inflammatory bowel diseases. Experimental evidence from mouse models suggests that H. pylori has evolved to skew the adaptive immune response towards immune tolerance rather than immunity, which promotes persistent infection on the one hand, and inhibits auto-aggressive and allergic T-cell responses on the other. Regulatory T-cells mediating peripheral immune tolerance have emerged as key cellular players in facilitating persistent infection as well as protection from allergies, in both observational studies in humans and experimental work in mice. Recent data suggest that H. pylori actively targets dendritic cells to promote tolerance induction. The findings discussed in this review raise the possibility of harnessing the immunomodulatory properties of H. pylori for the prevention and treatment of allergic and auto-immune diseases, and also provide new insights relevant for H. pylori-specific vaccine development.